ENT300 Fundamental of Entrepreneurship. Business Plan : Pelangi Cake House / Siti Hamidah Abdul Kudus... [et.al] - Abdul Kudus, Siti Hamidah; Mohd Faizul, Nurul Farina; Jeliboh, Jessicia; Ikhwan, Lasminer; Kana, Shammilla; Kusam, Jacy (2014)
Our company name is Pelangi Cake House. In our business, we decided the partnership in our business. Each of the partnership has contributed certain amount of capital. The main business of activity is to serve the customer with good quality service and fulfill what the customer want. Our business focused on the quality of ours cake which can satisfy for the customer taste. We will open up the business at Desa Ilmu, Kota Samarahan, Sarawak. In our company we have own organization and divided to five subordinate. The five subordinate is administration manager (Jessicia Anak Jeliboh), marketing manager (Nurul Farina Binti Mohamad Faizul), operational manager (Shammilla Anak Kana and Lasminer Binti Ikhwan) and financial manager (Jacy Anak Kusam). The leader of ours company is General Manager. Our General Manager is (Siti Hamidah Binti Abdul Kudus). Our company has two operational managers which is operational manager one and operational manager two. The General Manager is responsible in planning, controlling, leading and organization. The administrative is manager responsible in preparing the marketing process that is identifying the target market, determining the of market, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies. The operational manager is to control and monitors the operation organization and last is financial manager where responsible in dealing with financial statement, balance sheet, handle every cash flow and financial transaction also the cost of production.